Pistachio industry in Tunisia: Opportunities of improvement - Elloumi O.; Ghrab M.; Chelli-Chaabouni A.; Ben Mimoun M. (XVI GREMPA Meeting on Almonds and Pistachios, 2016)
Pistachio is an important nut crop well extended in the centre and the south of Tunisia. An important increase of growing area occurred during the last forty years using almost only one variety ‘Mateur’, selected in the North of the country. However, the productivity is still very weak under low annual precipitation, warm climate and deficient cultural practices. These limiting factors for pistachio yield increased also the alternate bearing phenomena. Consequently, efforts are being made to improve the productivity of pistachio. The effect of main endogenous and environmental factors and their interactions on yield and alternate bearing was analyzed. The chilling and heat requirement of the main cultivar ‘Mateur’ were estimated to determine the best growing zone for its cultivation. This paper presents the main endogenous and environmental factors associated to alternate bearing and discuss possible approaches to be used to improve productivity and reduce alternate bearing of pistachio.
16. Meeting of GREMPA (Groupe de Recherches Méditerranéennes pour l\'Amandier et Pistachier / Mediterranean Research Group for Almond and Pistachio), 2015/05/12-14, Meknes (Morocco)